Peran Komunikasi Efektif dan Efesien dalam Pembelajaran - Sepni Yanti (Peneliti.net, 2019)
Sending messages and ideas requires effective and efficient time. Students who are ready to receive messages will easily communicate with teachers and peers. The communication process is not as simple as imagined. Communication can be an obstacle in classroom learning. Communication skills are the ability of teachers to create a communicative climate between teachers and students in learning activities in accordance with learning objectives. Related to the learning process, communication is said to be effective if the message in this case is the subject matter can be received and understood, and generate positive feedback by students. This research method uses a literature review method, by collecting data and sorting and then giving conclusions. The results of this study indicate that effective and efficient communication plays an important role in the teaching and learning process, which ultimately results in better output.